Prodrug activation by a viral protease: evaluating combretastatin peptide hybrids to selectively target infected cells - Richter, Michael; Leuthold, Mila; Graf, Dominik Korbinian; Bartenschlager, Ralf; Klein, Christian D. (ACS medicinal chemistry letters, 2019)
Infections with flaviviruses such as dengue virus (DENV) are prevalent throughout tropical regions worldwide. Replication of these viruses depends on tubulin, a host cell factor that can be targeted to obtain broad-spectrum antiviral agents. Targeting of tubulin does, however, require specific measures to avoid toxic side-effects. Herein, we report the synthesis and biological evaluation of combretastatin peptide hybrids that incorporate the cleavage site of the DENV protease to allow activation of the tubulin ligand within infected cells. The prodrug candidates have no effect on tubulin polymerization in vitro and are 20-2000-fold less toxic than combretastatin A-4. Several of the prodrug candidates were cleaved by the DENV protease in vitro with similar efficiency as the natural viral substrates. Selected compounds were studied in DENV and Zika virus replication assays and had antiviral activity at subcytotoxic concentrations.
Gesehen am 21.10.2019